Awareness and Determinants of farmers participation in e-Marketing of Agricultural Commodities in India - KJ Raghavendra; Shiv Kumar; Amit Kar; Pramod Kumar; T M Kiran Kumar; Rashmi Singh; Prawin Arya (Indian Journal of Extension Education, 2023)
Integration of APMCs across the country through e-NAM was to augment price discovery and dissemination. The process of electronic marketing being new to the stakeholders, the awareness and constraints entailed herein are addressed. This study evaluates the extent of awareness among farmers about different processes of e-marketing, along with the determinants of their participation. A total of 240 farm households were selected randomly through multistage sampling for the primary survey. The result of the study infers that distance to the market and farm size of the farmers was the most important factors that determine farmers’ participation in e-marketing. Awareness about different e-marketing processes among farmers is relatively lower in Andhra Pradesh compared to Karnataka. The promotion of more participation to create an efficient marketing system there is a need for elaborated awareness about e-marketing among farmers and also increases the capacity building programmes to enhance knowledge about several process of trading.